Pre‐operative oral nutritional supplementation with dietary advice versus dietary advice alone in weight‐losing patients with colorectal cancer: single‐blind randomized controlled trial. Issue 3 (3rd January 2017) - Burden, Sorrel T.; Gibson, Debra J.; Lal, Simon; Hill, James; Pilling, Mark; Soop, Mattias; Ramesh, Aswatha; Todd, Chris
Abstract: Background: Pre‐operative weight loss has been consistently associated with increased post‐operative morbidity. The study aims to determine if pre‐operative oral nutritional supplements (ONSs) with dietary advice reduce post‐operative complications. Methods: Single‐blinded randomized controlled trial. People with colorectal cancer scheduled for surgery with pre‐operative weight loss >1 kg/3–6 months were randomized by using stratified blocks (1:1 ratio) in six hospitals (1 November 2013–28 February 2015). Intervention group was given 250 mL/day ONS (10.1 KJ and 0.096 g protein per mL) and dietary advice. Control group received dietary advice alone. Oral nutritional supplements were administered from diagnosis to the day preceding surgery. Research team was masked to group allocation. Primary outcome was patients with one or more surgical site infection (SSI) or chest infection; secondary outcomes included percentage weight loss, total complications, and body composition measurements. Intention‐to‐treat analysis was performed with both unadjusted and adjusted analyses. A sample size of 88 was required. Results: Of 101 participants, (55 ONS, 46 controls) 97 had surgery. In intention‐to‐treat analysis, there were 21/45 (47%) patients with an infection—either an SSI or chest infection in the control group vs. 17/55 (30%) in the ONS group. The odds ratio of a patient incurring either an SSI or chest infection was 0.532 ( P = 0.135 confidence interval 0.232 to 1.218) in the unadjusted analysis and when adjusted for random differences at baseline (age, gender, percentage weight loss, and cancer staging) was 0.341 ( P = 0.031, confidence interval 0.128 to 0.909). Pre‐operative percentage weight loss at the first time point after randomization was 4.1% [interquartile range (IQR) 1.7–7.0] in ONS group vs. 6.7% (IQR 2.6–10.8) in controls (Mann–Whitney U P = 0.021) and post‐operatively was 7.4% (IQR 4.3–10.0) in ONS group vs. 10.2% (IQR 5.1–18.5) in controls ( P = 0.016). Conclusions: Compared with dietary advice alone, ONS resulted in patients having fewer infections and less weight loss following surgery for colorectal cancer. We have demonstrated that pre‐operative oral nutritional supplementation can improve clinical outcome in weight losing patients with colorectal cancer.